DEVELOPMENT OF POWDERY MILDEW ON DIFFERENT WHEAT CULTIVARS - B. M. SINGH, T. R. SHARMA AND (Indian Phytopathology, 2002)
The development of Erysiphe graminis tritici on 24 wheat varieties was studied to determine incidence severity relationship. Powdery mildew which was first observed on the lower leaves was always more severe on third leaf and least on the first leaf in all varieties although infection rates were more on first leaf. Infection rates on the moderately resistant varieties CPAN 1676 and HO 2204 were less than half as compared to the susceptible variety HS 86. On VL 421, after an initially high infection rate, the epidemic progressed comparatively slowly. Mildew development on VL 616 continued at a uniform rate after delayed appearance. The incidence severity relationship was better characterized by the semilog equation as compared to linear equation. Disease incidence upto 73 and 56 per cent could be satisfactorily used in case of semilog and linear equations, respectively to determine powdery mildew severity under field conditions.